2018
DOI: 10.3389/fimmu.2018.02335
|View full text |Cite
|
Sign up to set email alerts
|

Immune Thymic Profile of the MOG-Induced Experimental Autoimmune Encephalomyelitis Mouse Model

Abstract: Multiple sclerosis (MS) is a chronic, immune-mediated, demyelinating disease that affects the neurons of the central nervous system. Activated T cells, specific for myelin epitopes, cross the brain barriers, and react against the myelin sheath, leading to demyelination. Since T cells are generated within the thymus, here we explored, in mice, the alterations occurring in this organ throughout the different phases of the disease. We induced experimental autoimmune encephalomyelitis (EAE) in C57BL/6 females and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 49 publications
1
3
0
Order By: Relevance
“…It has been previously reported that during EAE peak and chronic stages, there is a thymic atrophy with lymphocyte loss and increase in the percentage of natural regulatory T cells [22,27,28]. We showed that the thymic disturbance starts together with the first clinical symptoms of EAE and that thymocyte loss positively correlates with the increase of EAE clinical signs, e.g., disease score.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…It has been previously reported that during EAE peak and chronic stages, there is a thymic atrophy with lymphocyte loss and increase in the percentage of natural regulatory T cells [22,27,28]. We showed that the thymic disturbance starts together with the first clinical symptoms of EAE and that thymocyte loss positively correlates with the increase of EAE clinical signs, e.g., disease score.…”
Section: Discussionsupporting
confidence: 63%
“…Based on the disturbance in the thymic innervation of MOG peak thymus and in the recently reported thymic atrophy during the EAE model [22], we hypothesized that these changes would also be compromising the thymic microenvironmental compartment, eliciting a dysfunctional T-cell development along with the clinical evolution of EAE. 1) and in the peak (14 d.a.i +/− 1) of the disease.…”
Section: Thymic Innervation In Mice Developing Eaementioning
confidence: 99%
“…It also remains unclear why homeostatic changes in peripheral immune composition in Lxrβ − /− mice are nullified after EAE induction. Of interest, thymic involution and loss of cellularity are not only apparent in Lxrβ − /− mice but also after EAE immunization [18,34]. Moreover, Lxrαβ-deficient mice show spontaneous breakdown in self-tolerance and develop age-dependent systemic autoimmune disease [35].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, thymic and splenic involution was reported transiently in EAE, acutely post-intracranial TMEV infection, and during cuprizone-induced demyelination. 5 , 71–74 While one paper reported reduced B and T-cell counts in the spleen within 6 days post EAE induction, 75 another study reported that spleen involution in the EAE model is heterogenous and dependent on mouse strain, pathology, and time points measured. 76 …”
Section: Intracranial Pathologiesmentioning
confidence: 99%